Examining the association between food literacy and food insecurity - Begley, Andrea; Paynter, E.; Butcher, L.; Dhaliwal, Satvinder (MDPI, 2019)
© 2019 by the authors. Poor food literacy behaviours may contribute to food insecurity in developed countries. The aim of this research was to describe the apparent prevalence of food insecurity in adults at enrolment in a food literacy program and to examine the relationship between food insecurity and a range of independent variables. Individuals attending the Food Sensations® for Adults program in Western Australia from May 2016 to April 2018 completed a pre-program questionnaire (n = 1433) indicating if they had run of money for food in the past month (food insecurity indicator), frequency of food literacy behaviours, selected dietary behaviours, and demographic characteristics. The level of food insecurity reported by participants (n = 1379) was 40.5%. Results from multiple logistic regression demonstrated that behaviours related to planning and management, shopping, preparation, and cooking were all statistically independently associated with food insecurity, in addition to soft/soda drink consumption, education, employment status, and being born in Australia. The results are salient as they indicate an association between food literacy and food insecurity. The implications are that food insecure participants may respond differently to food literacy programs. It may be necessary to screen people enrolling in programs, tailor program content, and include comprehensive measures in evaluation to determine effect on the impact of food literacy programs on different subgroups.